Birds in the Daily Life of the Toba Indigenous People from the West of the Province of Formosa (Argentina) - Gustav F. Scarpa (Ethnobiology Letters, 2010)
Review of Birds in the Daily Life of the Toba Indigenous People from the West of the Province of Formosa (Argentina). Pastor Arenas & Gustavo Porini. 2009. Tiempo de Historia, Asunción. Pp. 300 + xxvi. $27.00 (paperback). ISBN 9789995381660.